2021
DOI: 10.3389/fpubh.2020.627001
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Impact of Monetary Easing Policies in Times of a Pandemic

Abstract: This article tests five major economies of the world, United Kingdom, Japan, Brazil, Chin and lastly, India, for the changes in the monetary policy decisions that have been implemented following the Covid-19 outbreak. The assessment was undertaken in the form of an event study analysis, further substantiated with a regression analysis conducted for exploring the significance of CPI and real GDP in predicting the policy interest rates in the economy. The results of the event study analysis presented that the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…The potential for the ocular route of transmission and the presence of the SARS-CoV-2 in ocular tissues has been recently investigated. Transfer of the virus to ocular tissues can take place mainly in four ways: (1) by direct exposure to virus containing infectious droplets, (2) by contaminated hands or fomites, (3) by spreading due to viremia to the lacrimal gland and other eye tissues with dense vascularity (controversial), (4) by spreading from the upper respiratory tract to the lacrimal sac via the NLC and from there to the eye (controversial) [ 7 ]. NLC, a functional natural canal that connects the eye and respiratory system, is the main route of transmission from the eye to the respiratory system [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The potential for the ocular route of transmission and the presence of the SARS-CoV-2 in ocular tissues has been recently investigated. Transfer of the virus to ocular tissues can take place mainly in four ways: (1) by direct exposure to virus containing infectious droplets, (2) by contaminated hands or fomites, (3) by spreading due to viremia to the lacrimal gland and other eye tissues with dense vascularity (controversial), (4) by spreading from the upper respiratory tract to the lacrimal sac via the NLC and from there to the eye (controversial) [ 7 ]. NLC, a functional natural canal that connects the eye and respiratory system, is the main route of transmission from the eye to the respiratory system [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of the virus to ocular tissues can take place mainly in four ways: (1) by direct exposure to virus containing infectious droplets, (2) by contaminated hands or fomites, (3) by spreading due to viremia to the lacrimal gland and other eye tissues with dense vascularity (controversial), (4) by spreading from the upper respiratory tract to the lacrimal sac via the NLC and from there to the eye (controversial) [ 7 ]. NLC, a functional natural canal that connects the eye and respiratory system, is the main route of transmission from the eye to the respiratory system [ 7 , 11 ]. In an experimental animal study published recently, it has been shown that the virus can replicate in conjunctival cells and cause viral pneumonia through the eye [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations